DECISION-MAKING PRINCIPLES IN THE MANAGEMENT OF TEAL ORGANIZATIONS - Ładysz, Jerzy (Management and Administration Journal, 2025)
Teal organizations are a progressive organizational model based on self-management, employee autonomy and decentralized authority. These organizations operate without traditional hierarchies, based on a self-managed structure and the empowering of individuals and teams to take responsibility for decisions through consultations and collective intelligence. The objective of the research was to develop a set of universal decision-making principles in the management of teal organizations. The research methods applied in the study include a systematic review of the literature, along with its critical analysis, observation and logical deduction. To achieve the objective of the research, a conceptual organizational structure diagram of the teal team, a conceptual organizational structure diagram of the teal organization and a set of 11 universal decision-making principles in the management of teal organizations were developed. The research results can be used by managers to improve decision-making process in their organizations, especially in the frames of remote and decentralized work, employee engagement, and the support of self-management and transparency. A promising direction of future research are digital tools and the integration of AI in the decision-making process.